Preparing elite athletes for the career after the career: the functions of mentoring programmes - Hallmann, K.; Breuer, C.; Ilgner, M.; Rossi, L. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The purpose of this research was to identify important functions of a mentoring programme in Germany targeted at elite athletes and how they facilitate the transition phase from sporting career to professional career. We adapted the Mentor Role Instrument by Ragins and McFarlin to sport. The newly created scale was assessed by means of principal component analysis (PCA) and validated with confirmatory factor analysis (CFA) with data collected from n = 80 (for the PCA) and n = 197 (for the CFA) elite athletes taking part in a mentoring programme. The results reveal that mentors fulfil the functions of a benefactor, counsellor, supportive friend, role model and accepting partner. The overall functions of the mentoring relationship had a significant positive impact on satisfaction with the support in transitioning into a professional career. A key implication is that mentoring is a well-received instrument in supporting athletes with the transition phase.